2020
DOI: 10.1155/2020/5758038
|View full text |Cite
|
Sign up to set email alerts
|

Too Real to Be Virtual: Autonomic and EEG Responses to Extreme Stress Scenarios in Virtual Reality

Abstract: The evolution of virtual reality (VR) technologies requires setting boundaries of its use. In this study, 3 female participants were experiencing VR scenarios with stressful content and their activity of the autonomic nervous system and EEG were recorded. It has been discovered that virtual reality can evoke acute stress reactions accompanied by activation of the sympathetic nervous system and a decrease in the activity of the parasympathetic nervous system. The high-stress response is accompanied by a decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 43 publications
(72 reference statements)
2
26
0
Order By: Relevance
“…Such inconsistency in the relationship between task complexity and beta-band power has not even been discussed in the VRE. Recently, researchers have successfully applied EEG systems together with consumer-level VR HMDs [43,44]. For example, Dey and colleagues employed a 32-channel portable EEG system with the HTC VIVE VR headset to generate an adaptive VR training system by collecting alpha-band activities in realtime [44].…”
Section: Task Complexity and Electroencephalographymentioning
confidence: 99%
See 1 more Smart Citation
“…Such inconsistency in the relationship between task complexity and beta-band power has not even been discussed in the VRE. Recently, researchers have successfully applied EEG systems together with consumer-level VR HMDs [43,44]. For example, Dey and colleagues employed a 32-channel portable EEG system with the HTC VIVE VR headset to generate an adaptive VR training system by collecting alpha-band activities in realtime [44].…”
Section: Task Complexity and Electroencephalographymentioning
confidence: 99%
“…Recently, researchers have successfully applied EEG systems together with consumer-level VR HMDs [43,44]. For example, Dey and colleagues employed a 32-channel portable EEG system with the HTC VIVE VR headset to generate an adaptive VR training system by collecting alpha-band activities in realtime [44]. Taking advantage of recent technological advancements in EEG devices that are portable and provide data in real-time [45,46], our second research question was to determine whether brain signals indicate task complexity in the VRE.…”
Section: Task Complexity and Electroencephalographymentioning
confidence: 99%
“…With the increase level of realism in a stressful VR environment, precaution must be taken to ensure extreme stress is not induced during the VR experience. Fadeev et al reported that VR with extreme stress scenarios can elicit autonomic and EEG responses due to high emotional stress [ 21 ]. Saghafian et al also suggested the need to measure realism with emotions within a stressful VR experience [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been used in various settings such as healthcare [ 9 , 10 , 11 , 12 ], oil production [ 13 , 14 ], workplace [ 15 ] and education [ 16 ]. With the integration of EEG, researchers have studied various brain functions such as attention [ 17 , 18 ], cognitive load [ 19 , 20 ], motor intention and planning [ 11 ], emotional processing [ 21 , 22 ], sense of immersion [ 23 , 24 ], engagement [ 25 ] and relaxation [ 26 , 27 , 28 ]. Although VR has been used with the EEG for meditation and mind therapy purposes, it has not been used as an integrated system to monitor mental health in workplaces.…”
Section: Introductionmentioning
confidence: 99%
“…VR immersion, especially containing stressful content, can evoke acute stress reactions accompanied by autonomic dysfunction [ 38 ]. Heart rate variability (HRV) is a sensitive indicator of cardiac autonomic modulation [ 39 ] and responds to any psychophysical changes immediately.…”
Section: Introductionmentioning
confidence: 99%